Counting outcomes, coverage and quality for early child development programmes. (18th March 2019) - Milner, Kate M; Bhopal, Sunil; Black, Maureen; Dua, Tarun; Gladstone, Melissa; Hamadani, Jena; Hughes, Rob; Kohli-Lynch, Maya; Manji, Karim; Ponce Hardy, Victoria; Radner, James; Sharma, Sonia; et al.
Abstract : Improved measurement in early child development (ECD) is a strategic focus of the WHO, UNICEF and World Bank Nurturing Care Framework. However, evidence-based approaches to monitoring and evaluation (M&E) of ECD projects in low-income and middle-income countries (LMIC) are lacking. The Grand Challenges Canada®-funded Saving Brains® ECD portfolio provides a unique opportunity to explore approaches to M&E of ECD programmes across diverse settings. Focused literature review and participatory mixed-method evaluation of the Saving Brains portfolio was undertaken using an adapted impact framework. Findings related to measurement of quality, coverage and outcomes for scaling ECD were considered. Thirty-nine ECD projects implemented in 23 LMIC were evaluated. Projects used a 'theory of change' based M&E approach to measure a range of inputs, outputs and outcomes. Over 29 projects measured cognitive, language, motor and socioemotional outcomes. 18 projects used developmental screening tools to measure outcomes, with a trade-off between feasibility and preferred practice. Environmental inputs such as the home environment were measured in 15 projects. Qualitative data reflected the importance of measurement of project quality and coverage, despite challenges measuring these constructs across contexts. Improved measurement of intervention quality and measurement of coverage, which requires definition of the numerator (ie, intervention) and denominator (ie, population in need/at risk), are needed for scaling ECD programmes. Innovation in outcome measurement, including intermediary outcome measures that are feasible and practical to measure in routine services, is also required, with disaggregation to better target interventions to those most in need and ensure that no child is left behind.